2016
DOI: 10.1007/s11033-016-4040-9
|View full text |Cite
|
Sign up to set email alerts
|

Expression of metalloproteinases (MMP-2 and MMP-9) in basal-cell carcinoma

Abstract: The aim of this study was to compare the expressions of mRNA for metalloproteinases (MMP-2 and MMP-9) and type IV collagen in two different histological types of basal-cell carcinoma (BCCs; nodular and infiltrative) and in normal tissues from the tumor interface. The study included biopsy specimens of the skin involved with BCC and normal skin adjacent the lesion. The expressions of mRNA for MMP-2, MMP-9 and type IV collagen were determined by means of RT-PCR (Reverse transcription polymerase chain reaction). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 53 publications
1
20
0
Order By: Relevance
“…In a recent study, expression profiling of BCCs showed an increase in ECM remodeling proteins including MMP-1, -3, -8, -9, and Cathepsin-K indicating the important role played by these enzymes in cancer progression (Ciazynska et al, 2018). In organ culture models of BCC the increased expression of MMP-2 and MMP-9 correlates with degradation of collagen-I and -IV at the tumor front (Goździalska et al, 2016). Likewise, the expression of ADAM-10, -12, and -17 was specifically observed in deep invasion area of BCC biopsies and correlated with the loss of collagen-XVII (Oh et al, 2009).…”
Section: Skin Diseasesmentioning
confidence: 99%
“…In a recent study, expression profiling of BCCs showed an increase in ECM remodeling proteins including MMP-1, -3, -8, -9, and Cathepsin-K indicating the important role played by these enzymes in cancer progression (Ciazynska et al, 2018). In organ culture models of BCC the increased expression of MMP-2 and MMP-9 correlates with degradation of collagen-I and -IV at the tumor front (Goździalska et al, 2016). Likewise, the expression of ADAM-10, -12, and -17 was specifically observed in deep invasion area of BCC biopsies and correlated with the loss of collagen-XVII (Oh et al, 2009).…”
Section: Skin Diseasesmentioning
confidence: 99%
“…MMPs are associated with tumor invasion and metastasis by degradation of the extracellular matrix. MMP2 and MMP9 degrade collagen IV, and the levels of MMP2 and MMP9 mRNA are significantly higher in nodular and infiltrative BCCs compared with normal adjacent tissue (37). In addition, MMP9 expression was significantly higher in infiltrative compared with nodular tumors.…”
Section: Discussionmentioning
confidence: 92%
“…[78,82] No difference in MMP-2 expression has been noted between different subtypes of BCC. [110] Expression of MMP-3 at mRNA and protein level is elevated in BCC tumors compared to unaffected tissue. [89,111] MMP-3 is expressed mainly by stromal fibroblasts and infrequently in sclerosing cancer islands.…”
Section: Mmps In Basal Cell Carcinomamentioning
confidence: 98%